(untitled) (The International Journal of Educational Sciences and Arts, 2025)
This study examines the linguistic structure and textual coherence of a poem that has achieved a level of prestige and fame unmatched by any other poetic text. It is Ka’b ibn Zuhair’s Lamiyat "Banat Su’ad." A linguistic analysis reveals the coherence and interconnectedness of its components. It is characterized by its well-defined linguistic structures. This study has prompted many scholars to pause and reflect on it. This study will focus on the sentence structure and its distribution within the communicative context of the poem, and will clarify the means used by the poet to achieve his main purpose, which was to forgive the Messenger of God, may God bless him and grant him peace, after his blood was shed. He was able, with his poetic talent, to achieve his goal through a captivating poetic style that enabled him to establish the foundation for embracing Islamic culture.